Smith and Roberson’s business law - Mann, Richard A. (South-Western Cengage Learning, 2009)
With a long history of accuracy and up-to-date coverage, SMITH AND ROBERSON'S BUSINESS LAW is the most complete and credible text available, equipping you with a thorough understanding of the key issues in business law. Completely updated, the new 14th edition of this classic features a comprehensive, detailed, and thorough presentation of business law issues ranging from traditional topics to new laws and emerging trends. End-of-chapter cases offer an excellent mix of landmark and current cases and include edited facts and decisions to preserve the language of the court, letting you apply the law to real business practice